2005
DOI: 10.1093/molbev/msi191
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Basal Angiosperm Node in Chloroplast Genome Phylogenies: Sampling One's Way Out of the Felsenstein Zone

Abstract: While there has been strong support for Amborella and Nymphaeales (water lilies) as branching from basal-most nodes in the angiosperm phylogeny, this hypothesis has recently been challenged by phylogenetic analyses of 61 protein-coding genes extracted from the chloroplast genome sequences of Amborella, Nymphaea, and 12 other available land plant chloroplast genomes. These character-rich analyses placed the monocots, represented by three grasses (Poaceae), as sister to all other extant angiosperm lineages. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
215
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 94 publications
16
215
1
Order By: Relevance
“…First, because using several taxa enables a better detection of multiple substitutions, increasing the taxon sampling is particularly important. All recent empirical phylogenomic studies [23,25,[28][29][30][31] except one [1] support this conclusion. This latter study [1] should be treated with caution because the tree used as reference (the MP nt tree of Figure 1a) is almost certainly incorrect.…”
Section: Conclusion and Recommendationsmentioning
confidence: 77%
“…First, because using several taxa enables a better detection of multiple substitutions, increasing the taxon sampling is particularly important. All recent empirical phylogenomic studies [23,25,[28][29][30][31] except one [1] support this conclusion. This latter study [1] should be treated with caution because the tree used as reference (the MP nt tree of Figure 1a) is almost certainly incorrect.…”
Section: Conclusion and Recommendationsmentioning
confidence: 77%
“…The sequence of nodes at the base of the tree of extant angiosperms is now known with a reasonable degree of confidence. Numerous studies have revealed strong support for the successive sister relationships of Amborellaceae, Nymphaeales [sensu APGII (3), including Hydatellaceae], and Austrobaileyales to all other extant angiosperms (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), although some studies have placed Amborellaceae ϩ Nymphaeales as sister to all other angiosperms (e.g., refs. 9 and 17).…”
mentioning
confidence: 99%
“…The increasing number of complete angiosperm plastid genome sequences presents an opportunity to explore whether character-rich data sets can resolve the relationships among these five major angiosperm lineages (13,14,30). Here we present phylogenetic analyses of 61 plastid protein-coding genes (Ϸ42,000 bp of sequence data) derived from complete plastid genome sequences of 45 taxa, including at least one member of every major basal lineage of angiosperms.…”
mentioning
confidence: 99%
“…Plant evolutionary biologists have long attempted to reconstruct angiosperm evolutionary history in an effort to determine the root of angiosperms. Since 1999, a series of molecular phylogenetic analyses have identified the monotypic Amborella, followed by Nymphaeales, or Amborella plus Nymphaeales, in the ANITA clade (Amborella, Nymphaeales, Illiciaceae, Trimeniaceae and Austrobaileyaceae) as representative of the most basal taxa (Mathews and Donoghue 1999;Parkinson, Adams, and Palmer 1999;Qiu et al 1999;Soltis, Soltis, and Chase 1999;Graham and Olmstead 2000;Qiu et al 2000;Zanis et al 2002;Borsch et al 2003;Zanis et al 2003;Stefanovic, Rice, and Palmer 2004;Leebens-Mack et al 2005;Chang et al 2006;Qiu et al 2006). In some cases, monocotbasal trees have also been reported (Goremykin et al 2003;Goremykin et al 2004;Chang et al 2006;Goremykin and Hellwig 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In reconstructing the phylogeny with molecular characters (protein and nucleotide sequences), two types of errors can cause phylogenetic discordance: 1) stochastic error resulting from sampling of limited and/or underrepresented characters and taxa and 2) systematic error generated by the presence of a nonphylogenetic signal in the data (Phillips, Delsuc, and Penny 2004;Jeffroy et al 2006). In the case of angiosperm phylogeny, because multi-gene concatenated samples and whole-chloroplast genomes of well-represented taxa have been analyzed (Stefanovic, Rice, and Palmer 2004;Leebens-Mack et al 2005;Chang et al 2006;Qiu et al 2006), the stochastic errors should be minimal. Therefore, the discordance among the trees appears to be mainly caused by systematic errors as different reconstruction methods consistently generate discordant, yet highly supported trees (Stefanovic, Rice, and Palmer 2004;Chang et al 2006;Jansen et al 2006;Jeffroy et al 2006;Qiu et al 2006).…”
Section: Introductionmentioning
confidence: 99%